Analisa Unjuk Kerja Radiator Sebagai Alat Pendingin Pada Mesin Mobil Isuzu Panther - hotlan panjaitan (Jurnal Rekayasa Sriwijaya, 2013)
Â  ABSTRACT The cooling system on the car serve to lower the temperature on the machine that results from combustion of fuels space. The cooling system on the engine using a tool that is in the form of Radiator. The issue will be examined in this final Task is to know is how much influence the speed of the air flow to the radiator's effectiveness. Based on analysis by using charts the relationship of air flow rate, cooling water temperature and effectiveness, that the value of the Radiator's effectiveness will be increased in proportion to the speed of the airflow. Based on the description that was submitted to be drawn the conclusion, there is the influence of air flow rate with the effectiveness of the Radiator.It can be proven that the value of the effectiveness of the radiator will increase thanks to increasing the speed of the flow of air vice versa the value of the effectiveness of the radiator tends to go down along with of decrease in velocity the flow of air. And from the result obtained and obtained from the analysis result of being counted the value of the effectiveness of the radiator namely 65,25 %. So that the performance of the radiator worked pretty well in discharging on motor fuel. Keywords: the radiator, effectiveness, cooling machine